(untitled) (Journal of Governance and Development (JGD), 2015)
The purpose of this study is to analyze the reformation of Malaysian budgeting system, specifically in the context of Malaysian federal agencies. Budget deficit in Malaysian economy has long been subjected to criticism for, among others, inefficiency, ineffectiveness accountability and poor performance. These issues have paved the way for budget reforms and reorganizations seeking to address the weaknesses and enhance the efficiency and performance of budgeting. This study can be regarded as the first attempt to explore the reformation of budgetary system in Malaysian government. The improvement of the budgeting performance is important in order to provide further impetus to the national agenda of socio-economic development, dynamic socio-economic environment, nation-building, globalization, competitiveness and the enabling mechanisms.